Keberpihakan al-Qur’an Terhadap Mustadh’afin - Iffatus Sholehah (Living Islam: Journal of Islamic Discourses, 2018)
Crisis problematic stereotypes that can not be separated from human life from the time of the Prophet until today, namely mustadh'afin. Mustadh'afin here normally understood by people who are weak as a group in the economy as poor, beggars, orphans, slaves and women. To some people, they are all considered groups were weak and helpless and stereotypes of this kind still exist today. Therefore, how the Qur'an as a guide to answer all of this human's life. Because the Qur'an always be the answer to all the problems that arise. Stated that the Qur'an has a feature on each of His verses, including their support to mustadh'afin. This study uses literature research. The purpose of writing this article to explain the teachings of Islam which can be said to be close to the favor of the underprivileged. To frame this study, the authors discuss a little more about the verses that speak of their support to mustadh'afin. Even this can be evidenced by the many verses that speak about mustadh'afin once talked to worship mahdhah (vertical worship), for example prayer, fasting, zakat and others. This shows that paying attention to the underprivileged as important as the obligation of prayer, fasting, pilgrimage and so on. Therefore, on the impartiality of the Qur'an against mustadh'afin will be discussed in this scientific article.